2009
DOI: 10.1038/nature08035
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation at 1q21.1 associated with neuroblastoma

Abstract: Common copy number variations (CNVs) represent a significant source of genetic diversity, yet their influence on phenotypic variability, including disease susceptibility, remains poorly understood. To address this problem in cancer, we performed a genome-wide association study (GWAS) of CNVs in the childhood cancer neuroblastoma, a disease where SNP variations are known to influence susceptibility 1,2 . We first genotyped 846 Caucasian neuroblastoma patients and 803 healthy Supplementary Information is linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
271
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(279 citation statements)
references
References 34 publications
5
271
0
3
Order By: Relevance
“…Genome-wide association studies (GWAS) have also identified additional germline genetic variants in neuroblastoma patients, including single-nucleotide polymorphisms in LIN28B, BARD1, and LMO1, among others [26][27][28][29] as well as other polymorphisms in other chromosomal regions yet to be fully characterized [30,31]. These polymorphisms occur relatively frequently in the general population and may contribute to the development of sporadic neuroblastoma, although the functional roles of these germline variants and other somatic alterations remain to be elucidated.…”
Section: Epidemiology and Geneticsmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have also identified additional germline genetic variants in neuroblastoma patients, including single-nucleotide polymorphisms in LIN28B, BARD1, and LMO1, among others [26][27][28][29] as well as other polymorphisms in other chromosomal regions yet to be fully characterized [30,31]. These polymorphisms occur relatively frequently in the general population and may contribute to the development of sporadic neuroblastoma, although the functional roles of these germline variants and other somatic alterations remain to be elucidated.…”
Section: Epidemiology and Geneticsmentioning
confidence: 99%
“…Emerging insights into the genetics of constitutional disease etiology demonstrate that germ line polymorphisms in the form of copy number variants (CNVs) (3,4), both de novo and inherited, are associated with diseases, including Alzheimer's, Parkinson, mental retardation, autism, and schizophrenia (5). CNVs also confer risk to developing cancers, such as neuroblastoma, and are enriched in Li-Fraumeni syndrome (6,7). Therefore, given the strong heritable nature of prostate cancer, we sought to detect clinically-informative prostate cancer risk CNVs in the setting of widespread prostate-specific antigen (PSA) screening, as practiced in the United States (8) and Western Europe (9).…”
mentioning
confidence: 99%
“…17,22 This program has been widely used by researchers and the results generated from the program are already publicized in papers. [22][23][24][25][26][27] Two other ways of verifying the accuracy of the identified CNVs involve comparing the results with the DGV databases in which information on previously reported CNVs is stored, or using another CNV identification program to compare the results with.…”
Section: Resultsmentioning
confidence: 99%